Back to our roots: A revival of a public health nursing service. (2nd February 2019) - Wheeler, Beverley
Abstract : This article provides a service review following the introduction of a new service delivery model for a community school nursing team. Challenges, results and outcomes are presented with an overview of stakeholder feedback and service user involvement and experience.